Professional and Social Problems of Young Researchers and Lecturers Based on the Opinion Poll Results (the case study of NTUU Igor Sikorsky Kyiv Polytechnic Institute) - Zhabin, S.O.; Vasilyev, G.S.; Kazmina, O.P.; Sosnov, O.S.; Beletsky, O.A. (Science and Innovation, 2024)
The research contains analysis of the on-line sociological study of young lecturers from Igor Sikorsky Kyiv Polytechnic Institute conducted in 2016. This study is a continuation and development of public opinion polls of young researchers of the NAS of Ukraine initiated in 2015. The analyzed data covers young researcher responses regarding patenting, publication activity, participation in international scientific cooperation, academic mobility, availability of technical facilities, equipment and materials at job places, satisfaction with monthly salary, satisfaction with research work and intentions regarding the future research carrier. The authors have compared the reported results with the previous studies of problems of young researchers from academic sector. The main problems are the lack of professional equipment and materials for research on a global level. Among the social problems, the most frequently mentioned ones are low salaries and no housing provision. It has been concluded that the creation of favorable conditions for professional research and educational activities of youth should be a priority of HR policy at both the government and the agency levels to preserve the young reserve of Ukraine’s science.